182k views
2 votes
-2(4 + 3y) = -2(4 + y)

User Tsee
by
4.0k points

2 Answers

6 votes


remove parentheses
-2(4+3y) = -4 - y
into
-8 - 6y = -4 - y
add 8 to both sides
-6y = -4 - y + 8
simply to 4 - y
-6y = 4 - y
add y to both sides
-6y + y = 4
simplify
-5t = 4
divide by both sides
y = -4/5
(if ur answer is something under simplify that’s ur answer)


User Candidasa
by
5.3k points
7 votes

Answer:

Explanation:

-8-6y=-8-2y

+2y +2y

-8-4y=-8

+8 +8

-4y=0

Y=0

User Kristian Domagala
by
5.7k points